Observational evaluation of preoperative, intraoperative, and postoperative characteristics in 117 Brazilian women without uterine prolapse undergoing vaginal hysterectomy - Osako MT; Osako T; Clemente EM; Batista FC; Batista CS (Dove Medical Press, 2012)
Claudio Sergio Batista,1 Takasi Osako,2 Eliana Mara Clemente,2 Fernanda Carvalhido Antonio Batista,3 Maurício Takeshi Janiques Osako41Department of Gynecology and Obstetrics of Faculty of Medicine of Petropolis, Petropolis, Rio de Janeiro, Brazil; 2Gynecology and Obstetrics, Casa Providencia Hospital, Petropolis, Rio de Janeiro, Brazil; 3School of Medicine of Technical Educational Foundation Souza Marques, Rio de Janeiro, Brazil; 4School of Medicine of University Gama Filho, Rio de Janeiro, BrazilBackground: Despite the introduction of minimally invasive approaches for various benign uterine problems, hysterectomy is often still performed abdominally, but the vaginal route should be used whenever possible. The aim of this study was to identify the preoperative, intraoperative, and postoperative characteristics of women undergoing vaginal hysterectomy in the absence of uterine prolapse.Methods: A prospective, descriptive, quantitative, noncomparative study was conducted in 117 women between August 2009 and February 2011 in Petropolis, Rio de Janeiro, Brazil. The women included had a uterine indication for hysterectomy, their surgeries were performed by the same team, and they were followed up for 12 months. An adapted Pelvic Organ Prolapse Quantification system was used to check for uterine prolapse.Results: The age range of the women was 33–59 years, uterine volume was 300–900 mL, and 73.50% has undergone prior cesarean section. The main indication for hysterectomy was uterine myoma (64.95%), with a surgery time of 30–60 minutes in 55 (59.82%) and 19 (15.98%) cases, respectively. Uterine volume reduction was performed in 41 (35.05%) cases, salpingectomy was the most common associated surgery (81.19%), and anesthesia was subdural (68.37%). Common intraoperative complications included bladder lesions (8.54%), with conversion to the abdominal route being necessary in one case (1.28%), and the most common postoperative complication being vaginal cupola granuloma (32.47%). There was a statistically significant relationship between surgery time and uterine volume (χ2 = 17.367; P = 0.002).Conclusion: This study suggests that vaginal hysterectomy is a safe surgical procedure in view of its good performance and low complication rate.Keywords: vaginal hysterectomy, surgical procedure, enlarged uterus, myoma, women